Current progress on plastic/microplastic degradation: Fact influences and mechanism. (1st July 2022) - Lin, Zhenyan; Jin, Tuo; Zou, Tao; Xu, Li; Xi, Bin; Xu, Dandan; He, Jianwu; Xiong, Lizhi; Tang, Chongjian; Peng, Jianwei; Zhou, Yaoyu; Fei, Jiangchi
Abstract: Plastic pollution, particularly non-degradable residual plastic films and microplastics (MPs), is a serious environmental problem that continues to worsen each year. Numerous studies have characterized the degradation of plastic fragments; however, there is known a lack of about the state of current physicochemical biodegradation methods used for plastics treatment and their degradation efficiency. Therefore, this review explores the effects of different physicochemical factors on plastics/MPs degradation, including mechanical comminution, ultraviolet radiation, high temperature, and pH value. Further, this review discusses different mechanisms of physicochemical degradation and summarizes the degradation efficiency of these factors under various conditions. Additionally, the important role of enzymes in the biodegradation mechanism of plastics/MPs is also discussed. Collectively, the topics discussed in this review provide a solid basis for future research on plastics/MPs degradation methods and their effects. Graphical abstract: Image 1 Highlights: UV could disrupt the molecular structure of MPs to produce –CO−, C–OH, and –CHOOH groups. Physicochemical degradation of MPs was caused by many factors. The degradation efficiency of MPs mainly depends on the type of microorganism. Microorganisms have selective degradation effect on different polymers. The biodegradation mechanism of MPs is conducted by the participation of enzymes.